1992
DOI: 10.1007/bf01307581
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between basal acid output and daily ranitidine dose required for therapy in Barrett's esophagus

Abstract: We prospectively evaluated basal gastric acid secretion in 42 consecutive patients with Barrett's esophagus to determine the optimal dose requirement for an H2-receptor antagonist in relation to the gastric acid secretory status of each patient. All patients with Barrett's esophagus had pyrosis and 31 of the 42 patients had erosive esophagitis. Mean extension of Barrett's epithelium was 6.9 cm (range 2-17 cm). Mean basal acid output for the patients with Barrett's esophagus was 8.0 +/- 5.2 meq/hr, which was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 24 publications
1
15
0
1
Order By: Relevance
“…Although the inhibition of gastric acid secretion is known to decrease the time that the oesophageal pH < 4, 8,[36][37][38] gastric acidity has received limited attention with respect to its potential underlying role in oesophageal acid exposure in GERD. [39][40][41][42][43][44][45] The present finding that cisapride decreases post-prandial oesophageal acid exposure in subjects with GERD agrees with previous findings by others, [11][12][13][14][15] who have attributed this action of cisapride to its motility effects on the lower oesophageal sphincter pressure, oesophageal peristalsis and gastric emptying. [11][12][13][14][15] Our present results, however, indicate that the decrease in oesophageal acidity can be explained by a cisapride-induced decrease in gastric acidity.…”
Section: Discussionsupporting
confidence: 92%
“…Although the inhibition of gastric acid secretion is known to decrease the time that the oesophageal pH < 4, 8,[36][37][38] gastric acidity has received limited attention with respect to its potential underlying role in oesophageal acid exposure in GERD. [39][40][41][42][43][44][45] The present finding that cisapride decreases post-prandial oesophageal acid exposure in subjects with GERD agrees with previous findings by others, [11][12][13][14][15] who have attributed this action of cisapride to its motility effects on the lower oesophageal sphincter pressure, oesophageal peristalsis and gastric emptying. [11][12][13][14][15] Our present results, however, indicate that the decrease in oesophageal acidity can be explained by a cisapride-induced decrease in gastric acidity.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies reported that the gastric acid secretion level in erosive esophagitis patients is higher than that in controls [2][3][4][5], although one study did not agree with this [6]. In particular, a study successfully demonstrated that gastric acid secretion is associated with erosive esophagitis independent of other well-recognized contributors for GERD, esophageal motility dysfunction such as disorders of the lower esophageal sphincter, or esophageal peristalsis [7].…”
Section: Introductionmentioning
confidence: 78%
“…There have been some reports with regard to gastric acid secretion in patients with BE [18,19]. Collen and Johnson [18] have reported that basal acid output in patients with BE was signifi cantly higher than that of normal subjects; however, in that study the male/female ratio and age differed between the groups.…”
Section: Gastric Acid Secretion In Patients With Bementioning
confidence: 95%